EVALUASI IMPLEMENTASI SIPD DALAM PENGANGGARAN DAERAH PADA BAGIAN AKUNTANSI DAN PELAPORAN BKAD KABUPATEN SUMBAWA - Adellya Dewi Mustika; Arya Zulfikar Akbar (Universitas Muhammadiyah Bengkulu, 2026)
Digital transformation through the Regional Government Information System (SIPD) is a crucial step toward creating more transparent and accountable regional financial management. This study aims to evaluate the Regional Government Information System (SIPD) in the budgeting process at the Accounting and Reporting Division of the BKAD Sumbawa Regency, using the Van Meter and Van Horn model as a framework. The research was conducted using a descriptive qualitative approach, collecting data through interviews with four key informants and system document studies. The results indicate that, from a regulatory standpoint, SIPD has been able to integrate the process from planning to reporting and strengthen budget discipline through automatic ceiling locking features. However, several obstacles remain in the field, such as unstable central servers and uneven technical capabilities among staff. To address these issues, implementers made adjustments such as working at night and peer-to-peer learning. A key finding of this research is the